Salivary Gland Choristoma of the Middle Ear in a Child: A Case Report - Jančíková, Jana; Šikolová, Soňa; Machač, Josef; Ježová, Marta; Pavlovská, Denisa; Urík, Milan (Ear, nose, & throat journal, 2021)
Salivary gland choristoma is an extremely rare middle ear pathology. We present the case of a 10-year-old girl with unilateral conductive hearing loss. Tympanotomy showed a nonspecific middle ear mass, absence of stapes, anomaly of incus, and displaced facial nerve. It was not possible to remove the mass completely. Histology confirmed salivary gland choristoma. The hearing in this case can be improved with a bone-anchored hearing aid.
Keywords: Hearing Aids; Child; incus; nemoci vnitřního ucha; stapes; Facial Nerve; Humans; lidé; střední ucho; středoušní protézy; choristom; Ear, Middle; Stapes; Hearing Loss, Conductive; Salivary Glands; Choristoma; Female; sluchové pomůcky; převodní nedoslýchavost; Medical Illustration; lékařské ilustrace; slinné žlázy; ženské pohlaví; Labyrinth Diseases; Incus; dítě; nervus facialis; Ossicular Prosthesis